(untitled) (International relations and international law Journal, 2024)
The article examines the transformation of Russian-Chinese interaction in Central Asia against the background of China’s growing presence in the region, which is particularly relevant in the context of global geopolitical changes and increasing international tensions. The purpose of the research is to critically analyze the relationship between the official discourse of strategic partnership and the actual dynamics of Russian-Chinese interaction in Central Asia. The work focuses on studying economic presence, transformation of migration processes, changes in military-political influence, and educational space. The methodological basis of the research consists of a comprehensive approach combining quantitative and qualitative methods of empirical data analysis for the period 2010-2023. Official statistical materials, interstate agreements, data from expert-analytical centers, and results of sociological research were used. Based on systematic analysis, the formation of an asymmetric rivalry model has been identified, where behind the facade of declared strategic partnership, there is a consistent replacement of Russian influence by Chinese presence, which is confirmed by quantitative indicators. The scientific significance of the research lies in the development of theoretical approaches to the analysis of Russian-Chinese relations, demonstrating the need for a differentiated consideration of global and regional levels of interaction. The work makes a substantial contribution to understanding the mechanisms of regional balance of power transformation and the peculiarities of major powers’ interaction at the regional level. The practical value of the results lies in their potential use in forming Russia’s foreign policy strategy in Central Asia and adjusting mechanisms for maintaining regional influence in conditions of growing competition with China. The practical significance of the research is determined by its value for developing balanced foreign policy by Central Asian states in conditions of increasing competition between Russia and China. The results of the work allow regional countries to optimize their participation in various integration projects, improve investment attraction mechanisms, and develop more effective strategies for multi-vector diplomacy. Key words: Russian-Chinese relations, Central Asia", asymmetric rivalry, regional influence, strategic partnership.